2020
DOI: 10.1039/c9ra06695k
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic SiC hollow fiber membranes for low fouling separation of oil-in-water emulsions with high flux

Abstract: The dry-wetting spinning technique involving immersion-induced phase inversion and dry-sintering was applied to prepare two types of SiC and Al2O3 hollow fiber membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 40 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…This finding can be explained by the hydrophilicity of the TiO 2 membrane, but also depends on the stability of the oil-in-water suspension. Even though these membranes showed similar oil removal rates, the permeability of the SiC membrane developed in this study was significantly higher than that of other SiC membranes [ 32 , 51 , 52 , 53 ], Al 2 O 3 [ 54 ], ZrO 2 -Al 2 O 3 [ 55 ], and TiO 2 [ 50 ] membranes. The enhanced permeability is beneficial for reducing investment costs and footprint of the membrane installations, two crucial aspects for the application of ceramic membranes in the treatment of oily wastewater, as in the food industry or in the enhanced recovery of oil and gas.…”
Section: Resultsmentioning
confidence: 61%
“…This finding can be explained by the hydrophilicity of the TiO 2 membrane, but also depends on the stability of the oil-in-water suspension. Even though these membranes showed similar oil removal rates, the permeability of the SiC membrane developed in this study was significantly higher than that of other SiC membranes [ 32 , 51 , 52 , 53 ], Al 2 O 3 [ 54 ], ZrO 2 -Al 2 O 3 [ 55 ], and TiO 2 [ 50 ] membranes. The enhanced permeability is beneficial for reducing investment costs and footprint of the membrane installations, two crucial aspects for the application of ceramic membranes in the treatment of oily wastewater, as in the food industry or in the enhanced recovery of oil and gas.…”
Section: Resultsmentioning
confidence: 61%
“…Improving the hydrophilicity of ceramic membranes is a commonly used approach to reduce fouling caused by organic compounds and microorganisms in the treatment of oily wastewater. 162 One way to enhance the hydrophilicity of the surface is through modification of the ceramic membrane with nanoscale materials such as ferric oxide (Fe 2 O 3 ), GO, TiO 2 , SiO 2 , ZrO 2 , and Al 2 O 3 , which has been shown to improve fouling resistance performance. 163 Moreover, using these materials can lead to increased flux, oil rejection, and reduced fouling.…”
Section: Fouling Mitigation On the Ceramic Membrane Surfacementioning
confidence: 99%
“…This is particularly relevant for anionic surfactant-stabilized oil emulsions, which experience repulsive and attractive forces between the oil droplets and the membrane surface depending on the pH relative to the IEP. A comparative study by Xu et al 162 investigated the performance of Al 2 O 3 and SiC membranes for oil/water separation and fouling build-up on the membrane surface through the MF process. The results showed that the SiC membrane exhibited higher anti-fouling resistance and permeate flux stability due to its higher hydrophilic properties, stronger repulsion, and ability to repel oil droplets through electrostatic repulsion.…”
Section: Fouling Mitigation On the Ceramic Membrane Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…SiC and Si 3 N 4 materials also have a very low IEP (close to SiO 2 ) and high chemical stability. Xu et al [141] compared the performance of alumina and SiC hollow fibre membranes for MF of O/W emulsion, the results indicated that the SiC membrane had a smaller pore size, but gave a higher flux due to a higher hydrophilic surface. In addition, a better anti-fouling ability was observed for the SiC membrane owing to electrostatic repulsion to oil.…”
Section: Surface Charged Ceramic Membranementioning
confidence: 99%